Profile of a Composite Based on Bacterial Cellulose and Polyvinyl Alcohol as a Drug Release Matrix for Tetracycline Hydrochloride - Sukmaningrum, Afif Dwi; Yuanita, Emmy; Dharmayani, Ni Komang Tri; Sudirman, Sudirman; Sudewianingsih, Ni Made; Ulfa, Maria (Jurnal Riset Kimia, 2024)
Bacterial cellulose (BC) is a natural polymer with good mechanical properties and hydrophilicity. Polyvinyl alcohol (PVA) is a synthetic polymer widely used in medicine. Both have been researched for their potential in drug release and acceptance. This study aims to determine the role of BC and PVA as drug release matrices for tetracycline hydrochloride (TCH), with additional fillers such as graphite (G) and TiO2. The results showed that the composites with BC matrix had lower mechanical properties than those with PVA matrix, with tensile strength values of 6.4075 and 17.446 MPa, respectively. However, the BC matrix was superior in porosity and swelling ability. The drug release testing of TCH from the composites showed that the appropriate model to describe drug release in BC matrix composites was in zero order, while the PVA matrix was in first order. The antibacterial activity of the composites on both matrices was tested against Staphylococcus aureus. The results indicate that both composites have potential applications in promising biomedical fields.